Methodology of Defining of the Radiation Therapy Components for Various Methods of Patients’ Treating Using Medical Linear Accelerators and Gamma-Therapeutic Devices - E. V. Titovich; M. N. Piatkevich; N. I. Makarava (Приборы и методы измерений, 2020)
One of the main factors affecting the effectiveness of radiation therapy is the constancy of the patient’s position on the treatment table created by immobilization devices of various designs and held throughout the entire irradiation procedure, which guarantees the accuracy of the delivery of the prescribed dose distribution. The purpose of the work was to establish the numerical values of the dominant components of a radiation therapy session for each of the irradiation techniques most commonly used in clinical practice of the radiation therapy.To determine the numerical values of the components of the radiation therapy session, the authors have measured each component for some clinical cases of patients’ irradiation placed. The patients had been diagnosed with the following malignant tumours: prostate cancer, breast cancer, lung cancer, head and neck tumours. More than 2000 individual measurements have been carried out with the help of such medical linear accelerators as "Clinac", "Unique", "Truebeam", and the gamma-therapeutic apparatus named "Theratron".The numerical values of the time spent on 3 groups of parameters of an irradiation session were established: the mechanical parameters of the radiation therapy equipment, the functional characteristics of the irradiation systems and the parameters that directly depend on the personnel involved in an irradiation procedure.According to the measurement results, the flow diagram for the procedures of verifying a patient’s position on the therapeutic table (2 different techniques), preceding their irradiation and the radiation therapy procedures themselves was proposed. It has been shown that a number of session components can run in parallel to each other thus optimizing the time spent by a patient in the treatment room.Using the obtained values of the time spent on the radiation session parameters it is possible to actualize the mathematical model that will allow the medical physicist to determine in advance the duration of the irradiation session at the stage of treatment planning and choose a radiation therapy technique taking into account the individual parameters of the irradiation session in each particular clinical case.